Ruthenium-doped Titania-pillared Clay for The Selective Catalytic Oxidation of Cyclohexene: Influence of Ru Loading - Ahmed Dali; Ilhem Rekkab-Hammoumraoui; Sanaa El Korso; Souheyla Boudjema; Abderrahim Choukchou-Braham (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2019)
A series of ruthenium-based catalysts supported on acid-activated montmorillonite (PILC) and interspersed with titanium (Ru/Ti-PILCs) were prepared with various amounts of ruthenium. Their catalytic performances in the selective oxidation of cyclohexene, using tert-butylhydroperoxide (TBHP) as oxidant were checked. The clay structure modification by acid activation and impregnation of transition metals resulted in an enhanced Lewis and Bronsted acidities. The Ru/Ti-PILCs materials were characterized using X-ray diffraction (XRD), surface area and pore volume measurements, surface acidity followed by Fourier transform infrared (FTIR) spectroscopy, chemical analysis, and Scanning Electron Microscopy (SEM). It was found that all catalysts can selectively oxidize cyclohexene through allylic oxidation leading mainly to 2-cyclohexene-1-one (Enone) as the major product, and 2-cyclohexene-1-ol (Enol) as secondary product. With the 5 %Ru/Ti-PILC, it was possible to reach 59 % cyclohexene total conversion, and 87 % selectivity into 2-cyclohexene-1-one and 13 % selectivity into 2-cyclohexene-1-ol.